Impacts of aerosol particles on the microphysical and radiative properties of stratocumulus clouds over the southeast Pacific Ocean - Twohy, C; Anderson, JR; Toohey, D; Andrejczuk, M; Andrejczuk, M; Adams, A; Lytle, M; George, R; Wood, R; Saide, P; Spak, S; Zuidema, P; et al. (2013)
The southeast Pacific Ocean is covered by the world's largest stratocumulus cloud layer, which has a strong impact on ocean temperatures and climate in the region. The effect of anthropogenic sources of aerosol particles on the stratocumulus deck was investigated during the VOCALS field experiment. Aerosol measurements below and above cloud were made with a ultra-high sensitivity aerosol spectrometer and analytical electron microscopy. In addition to more standard in-cloud measurements, droplets were collected and evaporated using a counterflow virtual impactor (CVI), and the non-volatile residual particles were analyzed. Many flights focused on the gradient in cloud properties on an E-W track along 20° S from near the Chilean coast to remote areas offshore. Mean statistics, including their significance, from eight flights and many individual legs were compiled. Consistent with a continental source of cloud condensation nuclei, below-cloud accumulation-mode aerosol and droplet number concentration generally decreased from near shore to offshore. Single particle analysis was used to reveal types and sources of the enhanced particle number that influence droplet concentration. While a variety of particle types were found throughout the region, the dominant particles near shore were partially neutralized sulfates. Modeling and chemical analysis indicated that the predominant source of these particles in the marine boundary layer along 20° S was anthropogenic pollution from central Chilean sources, with copper smelters a relatively small contribution. Cloud droplets were smaller in regions of enhanced particles near shore. However, physically thinner clouds, and not just higher droplet number concentrations from pollution, both contributed to the smaller droplets. Satellite measurements were used to show that cloud albedo was highest 500-1000 km offshore, and actually slightly lower closer to shore due to the generally thinner clouds and lower liquid water paths there. Thus, larger scale forcings that impact cloud macrophysical properties, as well as enhanced aerosol particles, are important in determining cloud droplet size and cloud albedo. Differences in the size distribution of droplet residual particles and ambient aerosol particles were observed. By progressively excluding small droplets from the CVI sample, we were able to show that the larger drops, some of which may initiate drizzle, contain the largest aerosol particles. Geometric mean diameters of droplet residual particles were larger than those of the below-cloud and above cloud distributions. However, a wide range of particle sizes can act as droplet nuclei in these stratocumulus clouds. A detailed LES microphysical model was used to show that this can occur without invoking differences in chemical composition of cloud-nucleating particles. © Author(s) 2013.